Review of Automated Machines towards Devising A New Approach in Developing Semi-Automated Grass Cutter - Sivarao, Subramonian; T.J.S, Anand; Ariff, Hambali; Minhat, Mohamad; Azni, Faizul (2010)
This article presents a review of researches done on the subject of automated tractor. An autonomous tractor is a vehicle that can operate without or with minimal human control, self-propelled and guided automatically along a desired path. The benefits from such a system are useful for agriculture industry by reducing labor cost and time, as well as improving output efficiency by eliminating human errors. Many researches and inventions have been made, with the results ranging from successful, encouraging to some that are impractical for commercial implementation for certain reasons. These implements include sensor, global navigation satellite system, machine vision, laser triangulation, ultrasonic transmitter and geomagnetic controller, as well as actuator and servo motor.